Orthogonal pinhole-imaging-based learning salp swarm algorithm with self-adaptive structure for global optimization - Wang, Zongshan; Ding, Hongwei; Yang, Jingjing; Hou, Peng; Dhiman, Gaurav; Wang, Jie; Yang, Zhijun; Li, Aishan (Frontiers in Bioengineering and Biotechnology, 2022)
Salp swarm algorithm (SSA) is a simple and effective bio-inspired algorithm that is gaining popularity in global optimization problems. In this paper, first, based on the pinhole imaging phenomenon and opposition-based learning mechanism, a new strategy called pinhole-imaging-based learning (PIBL) is proposed. Then, the PIBL strategy is combined with orthogonal experimental design (OED) to propose an OPIBL mechanism that helps the algorithm to jump out of the local optimum. Second, a novel effective adaptive conversion parameter method is designed to enhance the balance between exploration and exploitation ability. To validate the performance of OPLSSA, comparative experiments are conducted based on 23 widely used benchmark functions and 30 IEEE CEC2017 benchmark problems. Compared with some well-established algorithms, OPLSSA performs better in most of the benchmark problems.